Apostolepis parassimilis Lema & Renner, 2012 an objective synonym of A. tertulianobeui Lema, 2004 (Dipsadidae: Elapomorphini) - Costa, Henrique C.; Bérnils, Renato S. (Zootaxa, 2015)
Lema (2004) described Apostolepis tertulianobeui based on a single specimen (a young male) from “hinterland Minas Gerais state”. The holotype was originally housed in the collection of Instituto Pinheiros Produtos Terapêuticos S.A. and labeled as IP 1934 (Lema 2004). The Instituto Pinheiros was founded in 1928 in the city of São Paulo, Brazil and became the largest producer of vaccines and antitoxins of the country (Ribeiro 2001). It was purchased in 1972 by the company Sintex do Brasil (Edler 2006) and its former collection was partitioned among several institutions (Lema 2004). As a result, the specimen IP 1934 was donated to the collection of the Museu de Ciências Naturais from Fundação Zoobotânica do Rio Grande do Sul (MCN hereafter) in Porto Alegre, Brazil, and labeled as MCN 8535 (Fig. 1A–D).